ANALISIS PENGARUH KINERJA KEUANGAN, REALISASI BELANJA MODAL, DAN PENGELOLAAN MANAJEMEN ASET DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN (Survey Pada Pemerintah Daerah Kota Bengkulu) - Ersi Sisdianto; Nengsih Nengsih (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
Financial performance is a description of the achievement of the company's success can be interpreted as a result that has been achieved on various activities that have been done, Capital expenditure is the expenditure made in the framework of capital formation in the form of adding fixed assets / inventory that provides benefits over one accounting period. The management of regional assets in Decree of the Minister of Home Affairs No. 49/2001 is declared as a series of activities and actions on regional goods covering planning, determining needs, budgeting, standardization of goods and prices, procurement, storage, distribution, inventory, control, maintenance, security, utilization, Legal status and administration. Financial performance, capital expenditure realization has an influence on the quality of financial statements to be presented